Manure and tillage use in remediation of eroded land and impacts on soil chemical properties - Mikha, Maysoon M.; Benjamin, Joseph G.; Vigil, Merle F.; Poss, David J. (PloS one, 2017)
Soil loss through wind and water erosion is an ongoing problem in semiarid regions. A thin layer of top soil loss over a hectare of cropland could be corresponding to tons of productive soil loss per hectare. The objectives of this study were to evaluate the influence of beef feedlot manure, tillage and legume grass mixtures on changes in soil quality and nutrient components. The study was initiated in 2006 on an eroded site near Akron, Colorado, on a Norka-Colby very-fine sandy loam (fine-silty, mixed, mesic, Aridic, Argiustolls). Tillage treatments were no-tillage, shallow tillage (sweeps operations with V-blade) and deep tillage (DT; moldboard plow operations). In one set of plots, DT was implemented biannually (DT-2); and in another set the DT was done once at the initiation of the experiment in 2006. Amendments consisted of beef manure and urea (46-0-0), N fertilizer. Both amendments were added at low and high rates. A control treatment, with no fertilizer or manure added, was included with no-tillage and shallow tillage only. Six years of manure addition and tillage significantly altered soil chemical properties compared with fertilizer and grass legume mixtures. Across all the tillage treatments, at the 0-30 cm depth, soil pH from 2006 to 2012, was reduced 1.8 fold with high-manure compared with high-fertilizer treatment. Soil EC, Na, and SAR increased by 2.7 fold while soil P increase by 3.5 fold with high-manure treatment compared with low-manure from 2006 to 2012 across all the tillage treatments at the surface 0-30 cm. Soil organic carbon associated with high-manure was 71% higher than low-manure and 230% higher than high-fertilizer treatments in the 0-60 cm depth. Similar patterns were observed with soil total N. Overall, manure amendments greatly improved the soil nutrient status on this eroded site. However, the legume grass mixtures showed little effect on improving soils chemical properties. The micronutrients supplied by manure improved the soil nutrient status compared with inorganic fertilizer, the grass, and the grass-legume treatments. We concluded that more than six years are needed to measure significant improvements in soil quality from specific treatments, specifically fertilizer, grasses, and grass-legume mixtures in such eroded crop land.